Santos Dumont e o desenvolvimento da dirigibilidade de balões - Bizerra, Erivelton Alves (2008)
Alberto Santos Dumont (1873-1932) is well known in Brazil and France for his pioneer contributions to the development of the airplane. However, before that, he also helped to develop the technique of balloon flight, obtaining important results of directed flight using motorized airships. This works analyses his contribution to this field. This dissertation presents, first, an historical account of the invention of balloons, from the early Chinese flying lights to the introduction of hot-air and hydrogen balloons in Europe, in the 18th century. Next, this work analyses the issue of balloon flight control. After the first manned flights, in 1783, there was a strong interest for this invention and there were several proposals of controlling its flight. The first attempts of flying motorised balloons, which attained a moderate success, were made in 1852, using a heavy steam machine. Other attempts were made afterwards, using several kinds of motors (including electrical ones), but they did not attain practical results. In the late 19th century, Santos Dumont began to develop airships driven by internal combustion engines (such as those used by automobiles) and obtained good results. In 1901 he was awarded the Deutsch de la Meurthe Prize, when he demonstrated the control of a motorised balloon that was able to make a flight round the Eiffel Tower. Finally, this dissertation analyses Santos Dumont s scientific and technical knowledge, as well the technical difficulties involved in the control of airships, at that time